Performance Testing of DHT11 and DS18B20 Sensors as Server Room Temperature Sensors - Baehaqi, Mudofar; Rosyid, Abdul; Siswanto, Agus; Subiyanta, Erfan (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
Temperature is important parameter in many technological and scientific applications. Accurate temperature measurement is needed to monitor and control various processes, including in industry, agriculture, and in other system settings. There are several temperature sensors that can be used in measuring and monitoring microcontroller-based temperatures, for example DS18B20, DHT11, DHT22, LM35, SHT40, each of these sensors has advantages and disadvantages. In this study, we will discuss testing of two types of sensors, namely DHT11 and DS18B20. The performance of the two sensors will be tested, value of accuracy and the level of error in reading compared to tools commonly used in measuring temperature in the server room. The method used in this study is an experimental approach to compare the performance of the DHT11 and DS18B20 temperature sensors. The experimental approach allows us to perform tests and measurements directly on both sensors to obtain objective and accurate data. From the results of testing the temperature in the server room using the DHT11, DS18B20 sensors and compared with the Fluke 179 True-RMS Digital Multimeter, 10 trials were carried out, showing an average error value of 3.37 for the DHT11 sensor and 1.17 for the DS18B20 sensor. for the accuracy value of 96.63% for the DHT11 sensor and 98.83 for the DS18B20 sensor.